MODEL-MODEL PENGEMBANGAN KURIKULUM DAN SILABUS PEMBELAJARAN BAHASA ARAB - Ahmad Zubaidi (IAIN Ponorogo, 2015)
Abstract: Syllabus refers to a lesson plan on a particular or group of subjects/ themes that covers standard of competency, basic competencies, learning materials, learning activities, indicators of competence achievement, assessment, allocation of time, and learning resources. The principles in developing syllabus are scientific, relevant,systematic, consistency, adequate, actual and contextual, flexible, and comprehensive. The procedures of syllabus development are reviewing and determining standard of competency, assessing and determining basic competencies, determining indicators of competence achievement, identifying learning materials, determining the type of assessment, determining the allocation of time, and determining the source of learning. There are various models of syllabus on learning Arabic as a foreign language. Each model has a concept in teaching Arabic with its own framework and aspect of skills. ،ةءافكلا رايعم ىلع لمتشي ىذلا ةنيعلما سوردلا نم عجم وأ ام ةدام في هعورشمو سيردتلا جمانرب وه ررقلما نمزلاو ،ميوقتلاو ،تايافكلا هذه لىإ لوصولا تارشؤمو ،سيردتلا ةطشنأو ،سيردتلا داومو ،ةيساسلأا ةءافكلاو ةرصاعلما ،ةيئفكلاو ،ةيمظنلماو ،ةيبسانتلاو ،ةيملعلا :يهوررقلما ميمصت في سسأ ةثمو .ةساردلا رداصمو ،حاتلما ،ةءافكلا رايعم ينيعتو ةسارد :يه يساردلا ررقلما ميمصت تاوطخ امأ .ةيلومشلاو ،ةينورلماو ،ةيقايسلاو ينيعت ،ةيساردلا داولما شيتفت ،تايافكلا هذه لىإ لوصولل تارشؤلما ينيعت ،ةيساسلأا ةءافكلا ينيعتو ةسارد ةيبرعلا ةغللا ميلعتل يساردلا ررقلما نم عاونأ كانه .ةساردلا رداصم ينيعت مث نمزلا ديدتح ،ميوقتلا بولسأ هل نأ بنابج )ةيوغللا تاراهلماو ( ةيبرعلا ةغللا ميلعت قيبطت في ميهافم عونلا اذه نم لكلو .ةيبنجأ ةغلك.هيلإ دنتسي سسأ كلذك